2018
DOI: 10.1021/acs.est.7b04548
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Benzo[a]pyrene by Three Rainbow Trout (Onchorhynchus mykiss) Cell Lines and Extrapolation To Derive a Fish Bioconcentration Factor

Abstract: Permanent fish cell lines constitute a promising complement or substitute for fish in the environmental risk assessment of chemicals. We demonstrate the potential of a set of cell lines originating from rainbow trout ( Oncorhynchus mykiss) to aid in the prediction of chemical bioaccumulation in fish, using benzo[ a]pyrene (BaP) as a model chemical. We selected three cell lines from different tissues to more fully account for whole-body biotransformation in vivo: the RTL-W1 cell line, representing the liver as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 63 publications
(121 reference statements)
3
50
1
Order By: Relevance
“…dG- N 2 -BPDE). Although BaP metabolite formation was not determined in RTgill-W1 and RTgutGC cells after BaP exposure in the present study, RTgutGC cells have previously been shown to metabolise BaP (Stadnicka-Michalak et al, 2018), and the detection of BaP-derived DNA adducts (i.e. dG- N 2 -BPDE) (Fig.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…dG- N 2 -BPDE). Although BaP metabolite formation was not determined in RTgill-W1 and RTgutGC cells after BaP exposure in the present study, RTgutGC cells have previously been shown to metabolise BaP (Stadnicka-Michalak et al, 2018), and the detection of BaP-derived DNA adducts (i.e. dG- N 2 -BPDE) (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Stadnicka-Michalak et al (2018) observed similar moderate (~10%) effects on cytotoxicity (which was not significant in their study), in both these cell lines after BaP exposure for 48 h. Cytotoxicity of these pollutants is often associated with biotransformation which produces reactive metabolites and/or free-radicals (Imanikia et al, 2016; Banni et al, 2017; White et al, 2017; Jarvis et al, 2018; Reed et al, 2018). CYP1A1 enzyme activity in the RTgill-W1 cell line, as measured by ethoxyresorufin O-deethylase (EROD) activity, has been reported to be low and is not significantly induced by BaP (Stadnicka-Michalak et al, 2018), which may explain the low cytotoxicity to this PAH (present study) and extracts from oil contaminated sediment (Amaeze et al, 2015). To our knowledge, the cytotoxicity of 3-NBA has not been ascertained in RTgill-W1 and RTgutGC cell lines previously.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…One could argue that losses may also stem from biotransformation of the chemicals by the cells. Indeed, in a study to explore biotransformation for bioaccumulation prediction in fish, RTgill-W1 cells were shown to biotransform benzo(a)pyrene, albeit in the presence of 5% FBS in the exposure medium (Stadnicka-Michalak et al , 2018a). To what extent RTgill-W1 cells are capable of biotransformation within 24 h of exposure in L-15/ex is not yet known, though the relatively short exposure time combined with the simple nature of the medium suggests that biotransformation might, at minimum, be slowed.…”
Section: Discussionmentioning
confidence: 99%
“…46) The basic EROD activity and its induction by BaP are highest in RTL-W1, and the metabolic activity in the depletion of BaP decreases in the order of RTL-W1>RT gut GC>RT gill -W1. 47,48) Both the epifluorescence observation of treated cells and the GC-MS analysis of cell extracts clearly indicated the uptake of BaP by the RT gut GC cells. 49)…”
Section: Cell Linesmentioning
confidence: 97%